Identifikasi Jenis Resort Di Sumatera Utara Melalui Website Resort: Studi Kasus Simalem Resort Dan Mariana Resort - Akmal, Rifki; Anastassya, Arimbi; Harpan, Jhodil Khoir; Shanorra, Tania Tita; Hanafi, M. Imam; Chaidir, Muhammad (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
North Sumatra has excellent tourism potential, one of which is Lake Toba, which is included in the 10 National Priority Tourism Destinations. To support tourism development, quality accommodation is an important factor, including resorts that offer exclusive experiences for tourists. Two well-known resorts in the Lake Toba area are Marianna Resort and Simalem Resort. This study aims to compare the two as a reference for property developers in developing new resorts. This study uses a qualitative description method with 3A analysis (Attractions, Amenities, and Accessibility). Data were obtained through observation of the official websites of the two resorts and a literature review from the book